Research of Grinding Surface Roughness of Face Gear based on Analysis of Orthogonal Experiment - Liu Jinhua; Ming Xingzu; Gao Qin (Jixie chuandong)
The orthogonal experiment analysis of the surface roughness of grinding toothof face gear is carried out. The regression model of grinding wheel speed,feed rate and grinding depth is established by using multivariate nonlinear regression analysis method. The effect status of grinding wheel speed,feed speed and grinding depth on the face gear roughness are analyzed. The mathematical model of roughness about grinding wheel speed,feed speed and grinding depth is established. At last,according to the mathematical model of the single factor experimental data to carry on the comparison between measured and predicted,it is showed that the maximum error of the predicted value and the actual measured value is 11. 13%.The result shows that the relative error is not big,the accuracy of the model is improved.